2003
DOI: 10.1002/eji.200324342
|View full text |Cite
|
Sign up to set email alerts
|

Efficient generation and expansion of antigen‐specific CD4+ T cells by recombinant influenza viruses

Abstract: Adoptive transfer of in vitro generated antigen-specific T cells has been successfully used to treat viral infections in immunodeficient patients. Therefore, methods for the rapid in vitro expansion of antigen-specific T cells are needed. Influenza virus efficiently infects dendritic cells, and peptides derived from viral proteins are processed and presented to CD8 + cytotoxic T cells. However, both, CD4 + and CD8 + T cells are necessary for the efficient control of viral infections, and it is becoming increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…However, our inability to isolate infectious virus from any location other than the lungs suggested that the systemic dissemination of viral RNA was not associated with high-level replication. Instead, the systemic presence of viral RNA could indicate the migration of immune cells, including macrophages and dendritic cells, which are known to be infected by IAV and which may not support virus production (43,45,54). Indeed, viral RNA was found to be more widely distributed than infectious virus in previous studies (15).…”
Section: Discussionmentioning
confidence: 93%
“…However, our inability to isolate infectious virus from any location other than the lungs suggested that the systemic dissemination of viral RNA was not associated with high-level replication. Instead, the systemic presence of viral RNA could indicate the migration of immune cells, including macrophages and dendritic cells, which are known to be infected by IAV and which may not support virus production (43,45,54). Indeed, viral RNA was found to be more widely distributed than infectious virus in previous studies (15).…”
Section: Discussionmentioning
confidence: 93%
“…[15][16][17] However, biochemical and functional studies have shown that antigens localized within the cytoplasm can efficiently be processed for MHC class II-restricted presentation by human and murine antigen-presenting cells. [18][19][20][21] Several pathways involved in this process have been discussed and analyzed. Degradation of the proteins by the proteasome, translocation of epitopes from cytoplasm into membrane organelles, and autophagy were implicated in several experimental settings using defined antigens and delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…After 7 days of DC differentiation, the capacity for HLA-restricted presentation of the model antigen neomycin phosphotransferase was evaluated by determining the cytokine secretion of an antigen-specific CD4 + T-cell clone. 36 HLA-matched DC-precursor cells were incubated with gene vectorderived GM-CSF from transduced Raji cells or control supernatants and IL-4 as described before. Immature DCs were used for this experiment as they take up and process antigens most efficiently via phagocytosis.…”
Section: Dcs Differentiated With Vector-derived Gm-csf Stimulate T Cellsmentioning
confidence: 99%
“…In previous studies using this T-cell clone, GM-CSF secretion was found to be the most significant marker for T-cell activation. 36 As a positive control, a DP3-expressing lymphoblastoid cell line (LCL1.11) was loaded with the antigen (Figure 4c; gray closed bar). The results demonstrated that both the genevector-derived GM-CSF (black bar) and the exogenously added, recombinant cytokine (hatched bar) had the same effect on differentiation of DC precursor cells.…”
Section: Dcs Differentiated With Vector-derived Gm-csf Stimulate T Cellsmentioning
confidence: 99%